Specificity in change of direction training: impact on performance across different tests - Keiner, M.; Warneke, K.; Skratek, J.; Kadlubowski, B.; Beinert, K.; Wittke, A.; Wirth, K. (The Journal of Strength and Conditioning Research, 2025)
This study aimed to evaluate the specificity of change of direction (COD) training by investigating whether a targeted training protocol would yield superior adaptations when test and training exercises align, compared with standard soccer practice. Seventy-seven elite youth soccer players participated in a 4-arm, 4-week randomized intervention, with subjects completing 3 additional COD training sessions per week alongside their regular soccer training depending on their randomized group assignment. The training focused on either the 505, the Triangle, or the Curved Sprint COD tasks, while the control group did not receive any additional intervention. The results showed that COD training with cuts over 120° (Triangle and 505 intervention groups) led to significant (<0.05) performance improvements across all COD tests (Triangle, 505, and Curved Sprint). By contrast, the Curved Sprint intervention group improved only in the Curved Sprint test, and the control group showed no significant (p > 0.05) gains. However, sport-specific CODs vary significantly based on tactical and technical demands, making their precise definition and consequently the standardization of training challenging. Nonetheless, this study demonstrates that tailoring COD training to the specific movement requirements of the COD tests can effectively maximize performance improvements.